A new species of Larimichthys from Terengganu, east coast of Peninsular Malaysia (Perciformes: Sciaenidae) - Seah, Ying Giat; Hanafi, Norhafiz; Mazlan, Abd Ghaffar; Chao, Ning Labbish (Zootaxa, 2015)
A new species of Larimichthys from Terengganu, east coast of Peninsular Malaysia is described from specimens collected from the fish landing port at Pulau Kambing, Kuala Terengganu. Larimichthys terengganui can be readily distinguished from other species of the genus by having an equally short pair of ventral limbs at the end of the gas bladder appendages, which do not extend lateral-ventrally to the lower half of the body wall, and fewer dorsal soft rays (29–32 vs. 31–36) and vertebrae (24 vs. 25–28). Larimichthys terengganui can be distinguished from L. polyactis and L. crocea by having a gill raker at the angle of first gill arch shorter than the gill filament. Furthermore, the second anal spine in L. terengganui is equal or slightly shorter than eye diameter (vs. shorter in L. polyactis); L. terengganui has 8–9 anal soft rays (vs. only 7 in L. pamoides). Snout length of L. terengganui is greater than eye diameter, whereas in L. crocea the snout is shorter than eye diameter. A key to species of Larimichthys is provided. All obtained specimens of the species were recorded from Terengganu waters, east coast of Peninsular Malaysia.